COVID-19 AND CHILDREN’S CONCERNS IN LAW: ADOPTING A STRATEGIC VISION FOR GLOBAL RECONSTRUCTION AND ACCOUNTABILITY - Aderonke Esther Adegbite (UNISSULA, 2022)
This paper aims to explain why it is necessary for requisite bodies to be guided by over aching principles that rely on objective data, measures and various precedents. As at March 2020, over 50 (fifty) prominent organizations on the universal database were responding to the impact of Covid-19 on children. Without a strategic plan for global reconstruction and accountability, these bodies run the risk of being overwhelmed. This paper is qualitative; it examines contents and laws of both local and international authorities, then attempts to describe what a child related strategy for Covid-19 Pandemic entails. The initial activities should be at least to eradicate channels through which children get infected and die of the virus. The second is to reduce the negative socio economic effects of the virus and then the last process of streamlining current measures with existing efforts on Sustainable Development Goals. This last procedure covers activities that can accelerate the realization of the SDG 2030, despite the pandemic. That is where actions are subject to contemporary notions for inclusive development, equitable humanitarian intervention plans, and respect for the rights of children. At this period special attention should be on the impact of the Pandemic on vulnerable persons and low income nations.